Policy paper: South China Sea policy in the perspective of the United States and the perspective of China - Imam Budiman; Fauziah Muniroh Amini; Alifia Ramandha; Luthfiany Anindy; Yasmin Gasani Fadhlih; Fredy Efendy (Trigin Publisher, 2023)
This policy paper aims to propose policy options that the United States might choose regarding the situation in the South China Sea as well as options from China's own policies in addressing regional conflicts. The report will discuss policy recommendations, feasible policy options, state interests in the South China Sea and important background information of the area of concern. This research uses qualitative methods in this research using books, articles and journals as reference sources of research cited in accordance with the theme of this research which discusses the South China Sea dispute. While the approach used is a qualitative descriptive approachThe paper argues that the current US policy is holistic, thoughtful and reasonable. Any changes should be small and should follow the original principles defined in 1995 who has related to the conflict over claims in the South China Sea.